2016
DOI: 10.1002/ps.4306
|View full text |Cite
|
Sign up to set email alerts
|

Competition between the phytophagous stink bugs Euschistus heros and Piezodorus guildinii in soybeans

Abstract: The higher abundance of E. heros in neotropical soybean fields seems to result from higher competitive ability than its heterospecific competitor P. guildinii, which may prevent the higher losses caused by P. guildinii. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 46 publications
2
23
0
6
Order By: Relevance
“…Examination of insecticidal stress on non‐targeted pest species is lacking, despite its potential practical management consequences (Ripper, ; Hardin et al ., ; Guedes & Cutler, ). We therefore explored effects of insecticides used in soybean for controlling caterpillars and whiteflies on the mating behaviour and sexual fitness of the Neotropical brown stink bug, a pest of increasing status in Argentina and Brazil (Panizzi, ; Bueno et al ., ; Panizzi & Lucini, ; Tuelher et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Examination of insecticidal stress on non‐targeted pest species is lacking, despite its potential practical management consequences (Ripper, ; Hardin et al ., ; Guedes & Cutler, ). We therefore explored effects of insecticides used in soybean for controlling caterpillars and whiteflies on the mating behaviour and sexual fitness of the Neotropical brown stink bug, a pest of increasing status in Argentina and Brazil (Panizzi, ; Bueno et al ., ; Panizzi & Lucini, ; Tuelher et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In the new scenario of no-tillage/ multiple cropping, it has dramatically increased, expanding its range into most of the Brazilian territory and even invading Argentina (Saluso et al 2011). Recent studies conducted in the field indicated that E. heros is a superior competitor compared to P. guildinii in soybean (Tuelher et al 2016). Moreover, E. heros is considered more tolerant to insecticides than P. guildinii or N. viridula (Willrich et al 2003, Snodgrass et al 2005, which likely contributes to the prevalence of E. heros.…”
Section: Stink Bug Inter-specific Competitionmentioning
confidence: 99%
“…[21][22][23][24] This species is the prevailing stink bug pest species of South American soybean-growing fields. 23,25,26 The frequent overuse of neonicotinoid insecticides against this species leads to unintended sublethal effects 27,28 and control failures due to insecticide resistance. [21][22][23]29 In this study, we assessed the toxicity and evaluated whether the sublethal exposure of E. heros to imidacloprid [at 0.126 μg active ingredient (a.i.)…”
Section: Introductionmentioning
confidence: 99%